2014
DOI: 10.3811/jjmf.28.90
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis on Coating Weight Controllability of a Multi-slot Gas Wiping Nozzle

Abstract: This paper presents a study of the gas wiping process, which is used in coating processes to control the final coating weight applied on a substrate. Multi-slot type gas wiping nozzle was proposed for improving coating weight controllability, and investigated using numerical simulations recent years. We made two types of 3-slot wiping nozzle and measured 2-dimentional free-jet characteristics with a hot-wire anemometer. Then, gas wiping model experiments with paraffin wax coating were carried out. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…A previous study 9) by some of the same authors indicated that the distance between the main slot and the auxiliary slots has a remarkable influence on the formation of the jets after the three jets merge. In particular, wiping performance was improved by shortening the distance between the main slot and the auxiliary slots.…”
Section: -Slot Nozzlementioning
confidence: 95%
See 2 more Smart Citations
“…A previous study 9) by some of the same authors indicated that the distance between the main slot and the auxiliary slots has a remarkable influence on the formation of the jets after the three jets merge. In particular, wiping performance was improved by shortening the distance between the main slot and the auxiliary slots.…”
Section: -Slot Nozzlementioning
confidence: 95%
“…Although the simulation results indicated that the maximum impinging pressure of the 3-slot nozzle is higher than that of the 1-slot nozzle, the coating weight after wiping with the 3-slot nozzle was thicker than that after the 1-slot nozzle. Takeda et al 9) first investigated the jet flow characteristics and wiping performance of 3-slot nozzles in an experimental analysis with a paraffin wiping apparatus. The results showed that the jet formation after mixing of the three jets changes depending on the shape of the nozzle tips, and as a result, wiping performance might improve or deteriorate, depending on the nozzle design.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation